Diseño e implementación de un mecanismo de inversión de giro, como sistema contra accidentes para un trapiche de uso doméstico - Poma Cuenca, Mauricio Alexander (2023)
The research topic entitled "Design and implementation of a mechanism of inversion of rotation, as a system against accidents for a trapiche of domestic use"; aims to design and build a mechanism of inversion of rotation that is proposed as a proposal to prevent accidents in conventional trapiches, for this, a bibliographic research was conducted with the intention of defining construction parameters for such mechanism, based on this information collected design, build and select some of the parts and elements of the mechanism of inversion of rotation; Likewise, the sizing process was defined in each part and component, those that have sufficient working capacity according to the power offered by an engine of a domestic mill previously inspected in the locality; with this we obtained a mechanism of inversion of rotation, based on a system of gears, which has two transmission shafts (input and output power), through a validation process the correct functionality of the mechanism was verified, obtaining an inversion of rotation in the gear that connects with the rollers or masses of the mill previously analyzed. This system is maneuvered by a pedal, which consists of joints that transform a vertical movement into a horizontal movement that was coupled according to the operating conditions of the gear mechanism. With the help of the pedal, the gear set can offer the change of rotation, since in the power input shaft there is an intermediate gear (gear with free axial displacement) which connects either left or right with another gear to obtain a desired rotation in the power output shaft. Key words: trapiche, gear system, mechanical articulation, rotation reversal